M(IL-4) Tissue Macrophages Support Efficient Interferon-Gamma Production in Antigen-Specific CD8+ T Cells with Reduced Proliferative Capacity - Mulder, Rylend; Banete, Andra; Seaver, Kyle; Basta, Sameh (Frontiers in Immunology, 2017)
CD8+ cytotoxic T cell (CTL) responses are necessary for the lysis of virally infected cells and control of infection. CTL are activated when their TCR bind a MHC-I / peptide complex on the surface of antigen presenting cells such as macrophages (MΦ). It is now apparent that MΦ display remarkable plasticity in response to environmental signals to polarize into pro-inflammatory (M1) or anti-inflammatory (M2) MΦ. However, little is known regarding how MΦ activation status influences their antigen presentation function to CD8+ T cell in models of virus infection. Consequently, we tested how polarization of spleen derived (Sp)-MΦ impacts direct presentation of viral antigens to influence effector and proliferative CD8+ T cell responses. We show that M2 Sp-MΦ retain MHC I surface expression and the ability to stimulate IFN-g production by CTL following peptide stimulation and LCMV infection to levels similar to M0 and M1 MΦ. However, memory CD8+ T cells cultured in the presence of M2 MΦ underwent significantly reduced proliferation and produced similar IFN-g levels as co-culturing with M0 or M1 cells. Thus, these results show a novel ability of polarized MΦ to regulate CD8+ T cell proliferation and effector functions during virus infection.